PERAN DIGITALISASI TEKNOLOGI INFORMASI DALAM PROSES PENGEMBANGAN E-COMMERCE DI ERA 4.0 DAN SOCIETY 5.0 - Novitri Ramadhani; Diajeng Regita Nandani; Fachri Arrizki; Nurbaiti (EKSYA : Jurnal Ekonomi Syariah, 2023)
Limited sales activities have prevented a number of industries from developing properly. The size of the mobility and the liberalization of buying and selling, caused several parties to innovate to expand the market. The existence of E-Commerce can be a goal to produce a system that can provide convenience in introducing a product that you want to market. Expanding the reach of market share and ways to increase sales mobility by using ways to build an interactive communication relationship with consumers (customers). The results of the E-Commerce system design are expected to be able to display various information about the products sold by manufacturers. The E-Commerce sales system no longer only focuses on the local community, but can also serve foreign markets because of its unlimited reach through social media. The E-Commerce system makes it easy for visitors, in this case e-Commerce is designed to have a contribution in order to be able to solve problems to provide guaranteed information services that are closer to consumers (customers), display certain messages in providing directions to visitors, prospective buyers can make the order process, payment can be via transfer, cash on delivery and PayPal, and payment confirmation that has been made can be via contact person or via email. This fact can expand the reach of market share and also foster global competitiveness because the sales system is no longer limited to certain regions